Improving Availability in a Retail Laundry by TPM, 5S, and Standardized Work: An Empirical Research - Oliva Rivera, Fabian (2024)
The research aimed to develop a maintenance model for a retail laundry using TPM, 5S, and standardized work to improve availability. The literature review discusses autonomous maintenance as a key component of TPM, which aims to eliminate downtime due to machine breakdowns and involves employees in maintenance activities. The research was pre-experimental and found that the leading causes of low availability were the need for a maintenance plan, poor training, and disorganization. A pilot plan was implemented, resulting in a 7% increase in availability from 75% to 82%. The study's results support the effectiveness of the maintenance model developed. The study highlights the importance of good machinery maintenance management and organization in the laundry business. © 2024 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.